Isolated short CTG/CAG DNA slip-outs are repaired efficiently by hMutSbeta, but clustered slip-outs are poorly repaired - Panigrahi, G; Slean, M; Simard, J; Gileadi, O; Pearson, C (National Academy of Sciences, 2010)
Expansions of CTG/CAG trinucleotide repeats, thought to involve slipped DNAs at the repeats, cause numerous diseases including myotonic dystrophy and Huntington's disease. By unknown mechanisms, further repeat expansions in transgenic mice carrying expanded CTG/CAG tracts require the mismatch repair (MMR) proteins MSH2 and MSH3, forming the MutSbeta complex. Using an in vitro repair assay, we investigated the effect of slip-out size, with lengths of 1, 3, or 20 excess CTG repeats, as well as the effect of the number of slip-outs per molecule, on the requirement for human MMR. Long slip-outs escaped repair, whereas short slip-outs were repaired efficiently, much greater than a G-T mismatch, but required hMutSbeta. Higher or lower levels of hMutSbeta or its complete absence were detrimental to proper repair of short slip-outs. Surprisingly, clusters of as many as 62 short slip-outs (one to three repeat units each) along a single DNA molecule with (CTG)50*(CAG)50 repeats were refractory to repair, and repair efficiency was reduced further without MMR. Consistent with the MutSbeta requirement for instability, hMutSbeta is required to process isolated short slip-outs; however, multiple adjacent short slip-outs block each other's repair, possibly acting as roadblocks to progression of repair and allowing error-prone repair. Results suggest that expansions can arise by escaped repair of long slip-outs, tandem short slip-outs, or isolated short slip-outs; the latter two types are sensitive to hMutSbeta. Poor repair of clustered DNA lesions has previously been associated only with ionizing radiation damage. Our results extend this interference in repair to neurodegenerative disease-causing mutations in which clustered slip-outs escape proper repair and lead to expansions.